2008
DOI: 10.1007/s00540-008-0636-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral brachial plexus injury after liver transplantation

Abstract: We report a case of bilateral brachial plexus injury following living-donor liver transplantation. A 35-year-old man with hepatitis C cirrhosis underwent liver transplantation under general anesthesia, performed in the supine position with 90 degrees arm abduction. The surgery lasted for 14 h, and the anesthesia for 16 h. On postoperative day 1, it was noticed that he had brachial plexus injuries. We investigated the cause of the nerve injuries, in particular, the possible involvement of stretching, compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Four of these cases were due to the use of shoulder braces in the head-down position, three cases were due to improper positioning of the arm, and one case was due to sustained neck extension [2]. Hida et al [1] suggested that relatively frequent neurologic injuries during liver transplantation, including brachial plexus injury, were probably related to prolonged anesthesia, invasive central venous monitoring catheters, and surgical procedures such as veno-veno bypass and rib cage retraction. Even though we are aware of the risk of brachial plexus injury and we take precautions, these nerve injuries can still occur despite adequate padding of the affected nerve [6].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of these cases were due to the use of shoulder braces in the head-down position, three cases were due to improper positioning of the arm, and one case was due to sustained neck extension [2]. Hida et al [1] suggested that relatively frequent neurologic injuries during liver transplantation, including brachial plexus injury, were probably related to prolonged anesthesia, invasive central venous monitoring catheters, and surgical procedures such as veno-veno bypass and rib cage retraction. Even though we are aware of the risk of brachial plexus injury and we take precautions, these nerve injuries can still occur despite adequate padding of the affected nerve [6].…”
Section: Discussionmentioning
confidence: 99%
“…Jackson and Keats [3] reported that there was no noticeable effect when the arm was abducted to 90°. However, Hida et al [1] reported severe brachial plexus injury even when their patient's arms were abducted to 90°, which was considered safe. Michaels and Keats [7] reported three brachial plexus injuries after 113 consecutive radical retropubic prostatectomy cases with the arms secured laterally on arm boards.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations